EFFECT OF BRAND AWARENESS , BRAND ASSOCIATION , PERCEIVED QUALITY TO CONSUMER LOYALTY BLACKBERY’S SMARTPHONE IN MALANG - Suwanto, Antonius Budiman; Rosita, Nadiyah Hirfiyana (Jurnal Ilmiah Mahasiswa FEB, 2013)
This study aims to determine the effect of brand awareness , the brand association , perceived quality on consumer loyalty BlackBerry smartphone in Malang . This study uses a survey with the kind of explanatory research as it is meant to examine a number of independent variables on the dependent variable. Researchers using the classic test management , regression testing , and test the hypothesis of independent influence variables simultaneously or partially . The number of populations used in this study were 50 respondents to the characteristics of users of Blackberry smartphones old at least 17 years, with a life of at least 6 months and were in the city of Malang . With the distribution of questionnaires to 50responden investigators who meet the characteristics and through a variety of tests to determine the effect of brand awareness (X1), brand association (X2) , and perceived quality (X3) have a significant effect simultaneously or in part on consumer loyalty (Y). The results of this study indicate that the variable effect of brand association and perceived quality significantly affect consumer loyalty Blackberry smartphones in the city of Malang . Although variable brand awareness has not had a significant impact on consumer loyalty Blackberry smartphones in the city of Malang . Magnitude (R2 ) of the three independent variables on consumer loyalty in the city of Malang Blackberry smartphones is 64.2 %, while the remaining 35.8 % was influenced by other variables not examined in this study . Keywords: Consumer Loyalty , Brand Awareness , Brand Association , Perceived Quality